Wavelength-tunable single longitudinal mode fiber optical parametric oscillator - Lim, L. T.; Bakar, M. H. Abu; Mahdi, M. A. (Optical Society of America, 2017)
We demonstrate a ring cavity single longitudinal mode fiber optical parametric oscillator using a passive sub-ring cavity and an unpumped erbium doped fiber configured with an external fiber mirror for single mode selection. The unpumped erbium doped fiber uses its saturable absorption characteristic to generate a self-induced narrowband filter when two counter-propagating waves interfere inside the fiber. A single longitudinal mode laser is obtained with a linewidth of 17.35 kHz at a pump power of 31.2 dBm. A 3.8 nm tuning range from 1536.5 nm to 1540.3 nm is achieved with a signal-to-noise ratio of about 60 dB. The power stability of the single longitudinal mode laser is 2.07 dB over a period of 30 minutes.